Teknik Scrambel Dalam Meningkatkan Penguasaan Kosakata Bahasa Jepang Mahasiswa Akpar BSI Bandung - Fauzzia, Willma (Universitas Negeri Semarang, 2019)
Abstract _____________________________________________________________ At present there are many teaching techniques derived from games which are then applied in the field of teaching, one of which is the Scrambel technique. Through this game the students compete to compile the vocabulary of the letters that have been randomized. This study uses a type of quasi-experimental research. The research design used in this study was